Hubungan SPL dan Klorofil-a dengan Hasil Tangkapan Ikan Layang (Decapterus sp.) Menggunakan Citra Satelit Aqua MODIS di Perairan Buton - Fajar Indah Ningsih; Muslim Tadjuddah; Naslina Alimina; Ahmad Mustafa; Abdullah Abdullah (Universitas Halu Oleo, 2021)
Remote sensing as the fastest solution for transmitting information about fishing areas through the approach of oceanographic parameters such as Sea Surface Temperature (SST) and chlorophyll-a (SSC). This study aimed at determining spatial and temporal dynamics of SST and SSC also its colerration with catch of mackerel scad (Decapterus sp.) in Buton Waters. Data of SST and SSC were obtained by Aqua MODIS satellite imagery while catch data was obtained from data of Wameo Coastal Fishing Port for the period of three years (2018-2020). Colerration between SST and SSC with catch of mackerel scad were analyzed using rank spearman colerration by SPSS 16.0 programs. Spatial distribution of higest SST was disposed in Buton Strait and Muna Strait, the lower temperature was in South of Muna Strait and moved to the Wakatobi Waters while temporal distribution of SST ranged 29.96°C-26.23°C. Spatial distribution of higest SSC was disposed in Kapota Island Waters, Kaledupa Island, Tomia Island and Muna Strait, the lower SSC was in South of Buton Strait and moved to the North of Wakatobi Waters, while temporal distribution of SSC ranged 0.411 mg/m3-0.149 mg/m3. The colerration number between SST and catch of mackerel scad in 2018 was -0.154, in 2019 was 0.189 and in 2020 was 0.134 which means it has weak colerration while the SSC in 2018 was 0.357, in 2019 was -0.357 and in 2020 was -0.280 which means it has quite strong colerration.This research suggests further research is needed on the relationship of other oceanographic factors such as currents and waves to the catch of kites (Decapterus sp.) using satellite imagery in buton waters.